Development of an in vitro biofilm model for the study of the impact of fluoroquinolones on sewer biofilm microbiota - Naudin, Sarah A.; Ferran, Aude A.; Imazaki, Pedro Henrique; Arpaillange, Nathalie; Marcuzzo, Camille; Vienne, Maïna; Demmou, Sofia; Bousquet-Mélou, Alain; Ramon-Portugal, Felipe; Lacroix, Marlene Z.; Hoede, Claire; Barret, Maialen; et al. (Frontiers in Microbiology, 2024)
Sewer biofilms are likely to constitute hotspots for selecting and accumulating antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs). This study aimed to optimize culture conditions to obtain in vitro biofilms, mimicking the biofilm collected in sewers, to study the impact of fluoroquinolones (FQs) on sewer biofilm microbiota. Biofilms were grown on coupons in CDC Biofilm Reactors®, continuously fed with nutrients and inoculum (1/100 diluted wastewater). Different culture conditions were tested: (i) initial inoculum: diluted wastewater with or without sewer biofilm, (ii) coupon material: concrete vs. polycarbonate, and (iii) time of culture: 7 vs. 14 days. This study found that the biomass was highest when in vitro biofilms were formed on concrete coupons. The biofilm taxonomic diversity was not affected by adding sewer biofilm to the initial inoculum nor by the coupon material. Pseudomonadales, Burkholderiales and Enterobacterales dominated in the sewer biofilm composition, whereas in vitro biofilms were mainly composed of Enterobacterales. The relative abundance of qnrA, B, D and S genes was higher in in vitro biofilms than sewer biofilm. The resistome of sewer biofilm showed the highest Shannon diversity index compared to wastewater and in vitro biofilms. A PCoA analysis showed differentiation of samples according to the nature of the sample, and a Procrustes analysis showed that the ARG changes observed were linked to changes in the microbial community. The following growing conditions were selected for in vitro biofilms: concrete coupons, initial inoculation with sewer biofilm, and a culture duration of 14 days. Then, biofilms were established under high and low concentrations of FQs to validate our in vitro biofilm model. Fluoroquinolone exposure had no significant impact on the abundance of qnr genes, but high concentration exposure increased the proportion of mutations in gyrA (codons S83L and D87N) and parC (codon S80I). In conclusion, this study allowed the determination of the culture conditions to develop an in vitro model of sewer biofilm; and was successfully used to investigate the impact of FQs on sewer microbiota. In the future, this setup could be used to clarify the role of sewer biofilms in disseminating resistance to FQs in the environment.